Evaluasi dan Perbaikan Usability Aplikasi Mobile Ojesy Menggunakan Metode Usability Testing dan Use Questionnaire - Sri Wulandari Ningrum; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ojesy is an application that provides online transportation services to meet customer needs among women and children. The service is in the form of bike and courier services. The Ojesy application has been downloaded ten thousand times, but many users have negative reviews related to interface problems, lack of menu features, invisible driver points available, difficult address detection so filling in addresses manually and some the user is confused to see the estimated cost. Based on these users reviews, is a reffering to usability problems. Usability is an important aspect of measuring application quality which is a benchmark for determining the extent to which a product can be used by the user to reach the destination and how easy it is to use the application's interface. Usability measurement of this study uses the usability testing method where the evaluation process is carried out directly on the sample user. This test has three stages, the first task scenario test, the second completes the questionnaire and the third interview. Testing also uses a USE questionnaire that includes four parameters, namely usefulness, ease of use, ease of learning and satisfaction. Each parameter has several statements given to the user to assess the level of usability of the Ojesy application. The test was conducted twice, that is initial test to analyze the level of usability and problems before being given a recommendation. Then the final test is recommended for improvements in the form of a prototype using the material design guidelines to get good results, and tested again to get the final usability value. The results of the usability values ​​of the initial usability measurements were 42.75% and the final usability value after recommendations for interface improvement of 80.75%.